Simultaneous blockade of 5-HT1A/B receptors and 5-HT transporters results in acute increases in extracellular 5-HT in both rats and guinea pigs: in vivo characterization of the novel 5-HT1A/B receptor antagonist/5-HT transport inhibitor SB-649915-B. - Hughes, Z; Starr, K; Scott, C; Newson, M; Sharp, T; Watson, J; Hagan, J; Dawson, L (2007)
RATIONALE: The delay in onset and treatment resistance of subpopulations of depressed patients to conventional serotonin reuptake inhibitors has lead to new drug development strategies to produce agents with improved antidepressant efficacy. OBJECTIVES: We report the in vivo characterization of the novel 5-HT(1A/1B) autoreceptor antagonist/5-HT transporter inhibitor (6-[(1-{2-[(2-methyl-5-quinolinyl)oxy]ethyl}-4-piperidinyl)methyl]-2H-1,4-benzoxazin-3(4H)-one), SB-649915-B. MATERIALS AND METHODS: Ex vivo binding was used to ascertain 5-HT(1A) receptor and serotonin transporter occupancy. 8-OH-DPAT-induced hyperlocomotion and SKF-99101-induced elevation of seizure threshold were used as markers of central blockade of 5-HT(1A) and 5-HT(1B) receptors, respectively. In vivo electrophysiology in the rat dorsal raphe and microdialysis in freely moving guinea pigs and rats were used to evaluate the functional outcome of SB-649915-B. RESULTS: SB-649915-B (1-10 mg/kg p.o.) produced a dose-related inhibition of 5-HT(1A) receptor radioligand binding and inhibited ex vivo [(3)H]5-HT uptake in both guinea pig and rat cortex. SB-649915-B (0.1-10 mg/kg p.o.) reversed both 8-OH-DPAT-induced hyperlocomotor activity and SKF-99101-induced elevation of seizure threshold in the rat, demonstrating in vivo blockade of both 5-HT(1A) and 5-HT(1B) receptors, respectively. SB-649915-B (0.1-3 mg/kg i.v.) produced no change in raphe 5-HT neuronal cell firing per se but attenuated the inhibitory effect of 8-OH-DPAT. Acute administration of SB-649915-B resulted in increases (approximately two- to threefold) in extracellular 5-HT in the cortex of rats and the dentate gyrus and cortex of guinea pigs. CONCLUSIONS: Based on these data, one may speculate that the 5-HT autoreceptor antagonist/5-HT transport inhibitor SB-649915-B will have therapeutic efficacy in the treatment of affective disorders with the potential for a faster onset of action compared to current selective serotonin reuptake inhibitors.